Relationship Symptom Management Family as Caregivers of Post-Stroke Through Dorothea Orem's - Wulandari, Dewi; Ixora, Ixora; Yulidaningsih , Elok (Health Access Journal, 2026)
The aim of this study was to determine the relationship between symptom management by families as caregivers and the independence of Activities of Daily Living post-stroke clients at the Gondang Community Health Center in Tulungagung Regency using Dorothea Orem's theoretical. The research design was correlational with a cross-sectional approach. Independent variable of family symptom management. Dependent variable of ADL independence of post-stroke patients. The study population of families of Post-Stroke sufferers in the Gondang Community Health Center area with a total of 30 stroke from January 2024 to March 2024, with a Saturated Sampling technique. The research instrument was a questionnaire, data analysis using the Spearman Rho test technique. The results of the study showed that most of the respondents carried out symptom management on post-stroke clients, namely 22 people (73.3%), as many as 12 respondents (40%) of their ADL independence were in the severe dependency category, as many as 10 respondents (33.3%) in the moderate category and as many as 7 respondents (23.4%) in the mild category. There is a relationship between symptom management by families as caregivers and ADL independence of post-stroke clients through the Dorothea Orem theory approach at the Gondang Community Health Center (0.002 <0.05).